EVALUATION OF CLINICAL AND ANATOMICAL CHARACTERISTICS AND PATHOLOGICAL FEATURES AT AN AUTOPSY FOR INTERNAL NON- COMMUNICABLE DISEASES IN ANIMALS - Dzhuraev, O.A.; Ismatova, R.A.; Navruzov, N.I. (Research Focus International Scientific Journal, 2026)
This article examines the unique clinical and anatomical manifestations and pathological findings of farm animals affected by internal non-communicable diseases. Despite the diversity of etiological factors, pathological changes in a number of non-communicable diseases can be similar. However, differences between individual cases are manifested only in the severity of the developing pathological process, its area, and the extent of the lesion.